Королева грез моих: [Лирич. песни и стихи, киносценарий] - Высоцкий Владимир Семенович (1993)
Экземпляры: РБ(2) (20200528) / Инвентарный номер: 26625 / Цена: 1000.00 / Авт.знак: В93 / ГРНТИ: 17.82 / ББК: 84(2Рос-Рус)6